Promoting Faculty Scholarship – An evaluation of a program for busy clinician-educators - Reader, Stacia; Fornari, Alice; Simon, Sherenne; Townsend, Janet (Revue canadienne de l'éducation médicale, 2015)
Background: Clinician educators face barriers to scholarship including lack of time, insufficient skills, and access to mentoring. An urban department of family medicine implemented a federally funded Scholars Program to increase the participants’ perceived confidence, knowledge and skills to conduct educational research. Method: A part-time faculty development model provided modest protected time for one year to busy clinician educators. Scholars focused on designing, implementing, and writing about a scholarly project. Scholars participated in skill seminars, cohort and individual meetings, an educational poster fair and an annual writing retreat with consultation from a visiting professor. We assessed the increases in the quantity and quality of peer reviewed education scholarship. Data included pre- and post-program self-assessed research skills and confidence and semi-structured interviews. Further, data were collected longitudinally through a survey conducted three years after program participation to assess continued involvement in educational scholarship, academic presentations and publications. Results: Ten scholars completed the program. Scholars reported that protected time, coaching by a coordinator, peer mentoring, engagement of project leaders, and involvement of a visiting professor increased confidence and ability to apply research skills. Participation resulted in academic presentations and publications and new educational leadership positions for several of the participants. Conclusions: A faculty scholars program emphasizing multi-level mentoring and focused protected time can result in increased confidence, skills and scholarly outcomes at modest cost.